Analysis of Muslim Cash Businesses From an Islamic Economic Perspective - Ach Goesli; Juhadi Juhadi; Fenny Damayanti Rusmana (International Journal of Economics, Management and Accounting (IJEMA), 2023)
This research is motivated by the basic values ​​of Islamic economics are a set of values ​​that are believed in with all faith, which will become the basis of the Islamic economic paradigm, including business. The purpose of this research is to find out the Islamic economic review of the Muslim fashion business. This research uses qualitative research methods. Based on the research results, it shows that basic values such as a good philosophical value, instrumental and institutional, are based on the Al-Qur'an and Hadith which are the two highest normative sources in the Islamic religion. This is the main thing that differentiates Islamic economics from conventional economics, namely the placement of religious teachings as the main source of economic knowledge. Business according to Islam can be interpreted as a series of business activities in various forms which are not limited by the amount (quantity) of ownership of assets (goods/services) including profits but are limited in the manner and acquisition and utilization of assets (halal and haram rules). With sharia control, business aims to achieve four things, namely target results (material profit and non-material benefits), growth which means continuing to increase, sustainability for as long as possible and the blessing of Allah SWT's pleasure.